2018
DOI: 10.2147/ijn.s162558
|View full text |Cite
|
Sign up to set email alerts
|

Nanostructured Ag<sup>+</sup>-substituted fluorhydroxyapatite-TiO<sub>2</sub> coatings for enhanced bactericidal effects and osteoinductivity of Ti for biomedical applications

Abstract: BackgroundPoor mechanical properties, undesirable fast dissolution rate, and lack of antibacterial activity limit the application of hydroxyapatite (HA) as an implant coating material. To overcome these limitations, a hybrid coating of Ag+-substituted fluorhydroxyapatite and titania nanotube (TNT) was prepared.MethodsThe incorporation of silver into the HA-TiO2 hybrid coating improves its antimicrobial properties. The addition of F as a second binary element increases the structural stability of the coating. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 39 publications
(30 citation statements)
references
References 66 publications
1
29
0
Order By: Relevance
“…XRD tests were used to examine the purity and crystalline structure. The phase compositions of the anodised samples were reported in our previous publications; 31,34 all the reections reproduced the standard patterns, including JCPDS#005-0682 for the Ti substrate and #021-1276 for rutile (Fig. 2c).…”
Section: Resultssupporting
confidence: 67%
“…XRD tests were used to examine the purity and crystalline structure. The phase compositions of the anodised samples were reported in our previous publications; 31,34 all the reections reproduced the standard patterns, including JCPDS#005-0682 for the Ti substrate and #021-1276 for rutile (Fig. 2c).…”
Section: Resultssupporting
confidence: 67%
“…14 The biocompatibility of oxygen induction TaON-Ag nanocomposite thin films has been confirmed using an MTT assay, according to previous publications. 14,31 However, the osteogenic ability of Ag composite thin-film materials has been investigated in only a few studies. Li et al reported a Agembedded hierarchical TiO 2 film, which exhibited excellent bioactivity and cytocompatibility, as a promising candidate for orthopedic and dental implants.…”
Section: Figurementioning
confidence: 99%
“…Similarly, Huang et al deposited hybrid coatings based on F − /Ag + co‐doped HAp and TiO 2 on Ti substrate by electrodeposition, obtaining nanostructured coatings composed of HAp without forming any other secondary phase. They demonstrated the obtainment of dense and uniform films with a surface of nanorods (diameters between 30 and 50 nm), characterised by enhanced HAp dissolution resistance, due to the fluorine incorporation and to the nanosized structure, and improved bonding strength.…”
Section: Bi‐substituted Hydroxyapatite Coatingsmentioning
confidence: 99%
“…Good osteoblasts morphology, adhesion, spreading and proliferation on doped coatings were demonstrated and, in particular, Zn/FHAp coatings were able to promote ALP expression, thanks to a simultaneous influence of nanostructured surface effects and ions release . Furthermore, Huang et al studied the biological properties of composite/hybrid coatings based on F/Ag co‐doped HAp and TiO 2 , in terms of cell viability and antibacterial features, highlighting improved biological activity and cytocompatibility, and a superior bactericidal effect against viable S aureus . In vitro cell tests were performed with MC3T3‐E1 cell line, confirming the material biocompatibility and no‐reverse effects on cell proliferation and osteoblastic differentiation, independently of Ag presence.…”
Section: Bi‐substituted Hydroxyapatite Coatingsmentioning
confidence: 99%